2021
DOI: 10.1093/eurheartj/ehab186
|View full text |Cite
|
Sign up to set email alerts
|

Immediate post-procedural functional assessment of percutaneous coronary intervention: current evidence and future directions

Abstract: Percutaneous coronary intervention (PCI) guided by coronary physiology provides symptomatic benefit and improves patient outcomes. Nevertheless, over one-fourth of patients still experience recurrent angina or major adverse cardiac events following the index procedure. Coronary angiography, the current workhorse for evaluating PCI efficacy, has limited ability to identify suboptimal PCI results. Accumulating evidence supports the usefulness of immediate post-procedural functional assessment. This review discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 87 publications
1
33
0
8
Order By: Relevance
“…Many studies showed that the prediction accuracy of FFR using DS was low (≤35%) (Park et al, 2012;Cho et al, 2014;Curzen et al, 2014). Angiography-derived FFR was invasive detection and ignored individual risk factors of patients to predict FFR (Kogame et al, 2020;Suzuki et al, 2020;Ding et al, 2021). With the development of predictive FFR technology, some studies, including case reports, have shown that other risk factors besides DS can also have a significant impact on the prediction of FFR.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies showed that the prediction accuracy of FFR using DS was low (≤35%) (Park et al, 2012;Cho et al, 2014;Curzen et al, 2014). Angiography-derived FFR was invasive detection and ignored individual risk factors of patients to predict FFR (Kogame et al, 2020;Suzuki et al, 2020;Ding et al, 2021). With the development of predictive FFR technology, some studies, including case reports, have shown that other risk factors besides DS can also have a significant impact on the prediction of FFR.…”
Section: Discussionmentioning
confidence: 99%
“… 30 , 31 , 33 Additionally, improved coronary flow after PCI might show other stenoses in the same coronary artery to be functionally significant as well, especially more distal lesions. 31 …”
Section: Practical Aspects and Patient Selectionmentioning
confidence: 99%
“…The cause for suboptimal and impaired post-PCI FFR-values is often located outside the stent. 31 It might be that patients at higher risk for future MACE or target vessel failure are also more likely to have suboptimal post-PCI FFR-values, regardless of any existing causal relationship. Although theoretically likely, it is currently unknown whether additional treatments based on suboptimal or impaired post-PCI FFR lead to better long-term outcomes.…”
Section: Practical Aspects and Patient Selectionmentioning
confidence: 99%
See 2 more Smart Citations